2017
DOI: 10.1039/c7ra10315h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanosilica content on the corrosion inhibition of composite coatings of a filled epoxy resin grafted with a hydrophobic fluoroalkylsilane: a dual critical concentrations interpretation

Abstract: Hydrophobic epoxy-resin composite coatings uniquely display double corrosion-inhibition extrema at nanosilica dual critical concentrations of 0–0.5 and ∼3 wt%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…is a kind of oxidation-type inhibitor 9 and can promote the surface passivation of carbon steels due to the formation of surface passive film. [10][11][12] In alkaline and neutral environments, the related reports involving the passivation function of NO 2 on the steel surface have been published repeatedly. [13][14][15][16][17][18] Lee et al, 13 Dong et al, 14,15 Valcarce and Vazquez 16 and Reffass et al 17 respectively reported the effectiveness of NO 2 on the surface passivation of carbon steels in synthetic tap water (pH 7.2), in simulated carbonated concrete pore solution (pH 12.0), in mixed alkaline solution containing Cl -(pH 13.9) and in mixed NaHCO 3 and NaCl solution (pH 8.3).…”
Section: Nomentioning
confidence: 99%
“…is a kind of oxidation-type inhibitor 9 and can promote the surface passivation of carbon steels due to the formation of surface passive film. [10][11][12] In alkaline and neutral environments, the related reports involving the passivation function of NO 2 on the steel surface have been published repeatedly. [13][14][15][16][17][18] Lee et al, 13 Dong et al, 14,15 Valcarce and Vazquez 16 and Reffass et al 17 respectively reported the effectiveness of NO 2 on the surface passivation of carbon steels in synthetic tap water (pH 7.2), in simulated carbonated concrete pore solution (pH 12.0), in mixed alkaline solution containing Cl -(pH 13.9) and in mixed NaHCO 3 and NaCl solution (pH 8.3).…”
Section: Nomentioning
confidence: 99%
“…Therefore, we speculated that RGO-IL composite was combined with the above advantages of IL and RGO to present a better corrosion protection [Eq. (2)(3)(4)]. [51,52] Fe þ Cl À !…”
Section: The Eis Measurements For Various Coatingsmentioning
confidence: 99%
“…However, the stability of the metal was affected by the corrosive environment, which a redox reaction could happen on metal surface or interior leading to the in thickness reduce and strength loss of metal‐based material. It further cause equipment aging and failure, resource waste, and environmental pollution . In consideration of corrosion was a severe and perennial problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, all impedance spectra present two capacitive loops at high frequency and intermediate frequency, respectively. The capacitive loop at high frequency is associated with the corrosion product film, whereas the capacitive loop at intermediate frequency is attributed to the double layer capacitance and charge transfer resistance . At the low frequency, an inductive response may be related to the relaxation process of adsorbed species, such as Mg(OH) + or Mg(OH) 2 .…”
Section: Resultsmentioning
confidence: 99%